Body adiposity status in teenagers and snacking habits in early childhood in relation to approximal caries at 15 years of age - ANITA ALM, CHRISTINA FÃƒÆ’Ã¢â‚¬Â¦HRAEUS, LILL-KARI WENDT, GÃƒÆ’Ã¢â‚¬â€œRAN KOCH, BOEL ANDERSSON-GÃƒ (IAPD and Blackwell, 2008)
The prevalence of overweight [age-specific body mass index (isoBMI) 25–29.9] and obesity (isoBMI30) in children is rapidly increasing in many countries around the word, including those in Europe